COMMUNICATION STRATEGY OF THE PUBLIC RELATIONS DIVISION OF LPM DINAMIKA IN DISSEMINATING ISLAMIC INFORMATION TO STUDENTS OF THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Faiz Ahmad Zidan; Nur Hanifah; Fahira Rahmah Hani; Atika Syalsabila Putri; Nanda Risani Raqiqah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study examines the Islamic public relations strategy implemented by the Student Press Organization (Student Press Institute or LPM) Dinamika in disseminating Islamic information to the academic community of the State Islamic University of North Sumatra (UINSU). The research observation was conducted at the LPM Dinamika headquarters using in-depth interview techniques. The rapid development of information technology and the rise of social media penetration demand that student organizations engaged in dakwah adapt effective communication methods to shape Islamic understanding among students. The research employed a qualitative approach with a case study design, focusing on LPM Dinamika’s digital public relations activities through the Instagram platform. Data collection was carried out through in-depth interviews with organization members, participatory observation of digital activities, and content analysis of published materials. The findings indicate that LPM Dinamika has successfully adopted Islamic public relations values in its digital communication practices by producing content that is informative, educational, and persuasive. This strategy reflects the application of core Islamic public relations principles such as truthfulness (ṣidq), trustworthiness (amānah), conveyance (tablīgh), and wisdom (faṭānah), as manifested in various content formats including Islamic articles, dakwah infographics, motivational quotes, and religious-themed storytelling videos. These public relations activities go beyond information delivery, fostering active student participation in dialogue, learning, and digital dakwah. The high level of audience engagement on LPM Dinamika's digital platforms highlights the effectiveness of its public relations strategy, particularly in building credibility and strengthening its reputation as a trusted campus press institution. This research contributes to the development of an Islamic public relations model in the digital era, especially in the context of student organizations at Islamic higher education institutions.